A study of store and retail attributes influencing the young Indian consumer buying decision. (2017) - Yadav, Shalini; Garg, S.K.
Retail is passing through a critical phase in India and many alternative channels and store formats have evolved in the recent times. The young consumers' preferences have changed in the past decades due to improvement in purchasing power, increased options for shopping and globalisation. In this scenario, the manufacturers and the retailers are always in a dilemma regarding the retail and the store design to enhance the appeal of their products and services to the consumers'. The aim of this study is to identify the store and retail attributes which are most sought after by the young consumers' and to gauge the overall satisfaction with the Indian retail environment. The data obtained was analysed using descriptive statistics and exploratory factor analysis (EFA). The results reveal that the Indian youth is price and quality sensitive; attributes like easy accessibility and convenient location are identified to be crucial.